SPE Middle East Oil and Gas Show and Conference 2011
DOI: 10.2118/141490-ms
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Neutron Monitoring of the First CO2 EOR Pilot in the Middle East

Abstract: Using borehole measurements to monitor carbon dioxide (CO2) floods in the reservoir is essential to properly understand the behavior of the injected fluids and the flow patterns. Pulsed Neutron logs provide essential measurements for the evaluation of saturation in the injectors, producers and observers. However, the CO2 environment is as yet uncharacterized in the industry. Hence, reliable inferences require that either the measurement is immune to the borehole environment or that the perturbation is minimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…They concluded that the minimum miscibility pressure (MMP) was 4630 psia, The optimum injection rates for immiscible and miscible CO 2 injection scenarios were 17,000 and 30,000 Mscf/day, respectively and oil recovery factor reach 36.59% [1]. Al-Aryani and others [61] have reported on the first CO 2 -EOR pilot test in the Middle East where pulsed neutron logging was used to monitor the performance of a CO 2 flood in one of the largest oil fields in Abu Dhabi, United Arab Emirates. The results of this test will be viewed with great interest based on the fact that it will have a significant impact on the application of CO 2 -EOR in many oil-rich countries in the Middle East with the potential for very large additional oil recoveries.…”
Section: Co 2 -Eor Flooding Projects and Case Studiesmentioning
confidence: 99%
“…They concluded that the minimum miscibility pressure (MMP) was 4630 psia, The optimum injection rates for immiscible and miscible CO 2 injection scenarios were 17,000 and 30,000 Mscf/day, respectively and oil recovery factor reach 36.59% [1]. Al-Aryani and others [61] have reported on the first CO 2 -EOR pilot test in the Middle East where pulsed neutron logging was used to monitor the performance of a CO 2 flood in one of the largest oil fields in Abu Dhabi, United Arab Emirates. The results of this test will be viewed with great interest based on the fact that it will have a significant impact on the application of CO 2 -EOR in many oil-rich countries in the Middle East with the potential for very large additional oil recoveries.…”
Section: Co 2 -Eor Flooding Projects and Case Studiesmentioning
confidence: 99%
“…Injecting CO 2 alone is found to cause early breakthrough of CO 2 along fracture direction (Figuera et al 2014), which necessitates corresponding modeling of injection/production adjustment strategies in advance (Luis et al 2016). It is suggested that flood breakthrough in multilayered, multi-well CO 2 flood system can be identified through pulse-neutron production logs combined with permeability from the magnetic resonance (Aryani et al 2011). Unlike miscible flooding, gas breakthrough is more predominant in immiscible flooding in which gas moves through high permeable channels as evidenced in Yaoyingtai oil field (Yuncong et al 2014).…”
mentioning
confidence: 99%